Framing Of CNN International’s Narrative on the 2025 Gaza Ceasefire through Entman’s Theory - Muhammad Syarif Hidayatullah; Muhammad Nur; Nur Latifatul Qalbi (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2025)
International media have extensively covered the ceasefire agreement reached between Hamas and Israel in October 2025, a critical juncture marked by both hope and profound uncertainty. This study examines how CNN International framed this agreement and the underlying context of the prolonged conflict. Using Robert Entman’s framing theory (Problem Definition, Causal Diagnosis, Moral Judgment, and Suggested Remedies) and a qualitative descriptive methodology, we analyze a news report and an analysis piece from CNN International on this topic. Data were collected through systematic reading and annotation, then analyzed using a thematic model aligned with Entman’s framework. The study reveals that CNN International consistently employed a narrative frame of “Celebration and Trepidation.” The media defined the core problem as the precarity of the truce and the high risk of failure due to structural uncertainties (disarmament, governance). The cause of the current success was attributed to US-led diplomacy, while the cause of the uncertainty was rooted in historical failures and the complexity of the political endgame. The media made a moral judgment through strategic empathy, balancing the joy of Israeli hostage families with the mass casualties in Gaza, and proposed solutions centered on logistical control and sustained US leadership for the transition and reconstruction phases. The implication of these findings for language studies is that discourse linguistics and critical discourse analysis (CDA) are effective tools for uncovering the strategic construction of balance and the subtle ideological biases in news texts. By analyzing narrative structure and contrasting emotional language, we demonstrate how language not only reports political realities but also shapes public perceptions of risk and governance in post-conflict scenarios.